Answer:
Step-by-step explanation:
Given the below quadratic equation in vertex form;
![y=(x+4)^2-2](https://img.qammunity.org/2023/formulas/mathematics/college/359sd9998x7wqw1bzplzkonv6v6qs4kkbu.png)
Recall that a quadratic equation in vertex form is generally given as;
![y=(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/high-school/h4kqjwwshdhi39of5qh206bvx52ti58zvg.png)
where (h, k) is the vertex of the parabola
If we compare both equations, we can see that h = -4 and k = -2, therefore the vertex of the given parabola is (-4, -2).
To determine two points to the left of the vertex, we'll choose x = -5 and x = -7.
When x = -5, let's find y;
![\begin{gathered} y=(-5+4)^2-2 \\ =(-1)^2-2 \\ =1-2 \\ =-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bymehzzymtvglnumszz7w7mba1fxamul63.png)
When x = -7, let's find y;
![\begin{gathered} y=(-7+4)^2-2 \\ =(-3)^2-2 \\ =9-2 \\ =7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c8fevufi7lcre3no4kydy3xnfphrz9z8om.png)
To determine two points to the left of the vertex, we'll choose x = -3 and x = -1.
When x = -3, let's determine the value of y;
![\begin{gathered} y=(-3+4)^2-2 \\ y=(1)^2-2 \\ y=1-2 \\ y=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g8zytqf8p80gf50p6dnb8z34acul2nlbpj.png)
When x = -1, let's determine the corresponding value of y;
![\begin{gathered} y=(-1+4)^2-2 \\ y=(3)^2-2 \\ y=9-2 \\ y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u0kght40wjtxgsgmhj14uvpnxmxuikjk35.png)
With the above points, we can go ahead and graph the parabola as seen below;